TANGGUNG JAWAB PENJUAL TERHADAP PERJANJIAN JUAL BELI LAPTOP MELALUI MEDIA INTERNET DI KOTA SEMARANG - Denis Putra Sinulingga, Dewi Hendrawati, Suradi (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
In the trade agreement via internet really was needed by the existence of the seller’s responsibility so the buyer can be protected by law. The seller responsible for the defect hidden on the goods sold. Based on the provisions from the Article 1504 KUHPerdata, in the practice was known the warranty term in the trade agreement, sellers must give the guarantee that their goods can function according to the aim of use. The sellers who offered the laptop via internet give the description or the picture of laptop and information about laptop, so there is a warranty from the seller towards the trade agreement in the laptop via internet. The research was carried out by using the juridical empirical approach method and specification was carried out with descriptively the analysis. The source and kind of data used are primary data and the secondary data. Data collection techniques use library research and field studies, and the data are received will be analysed qualitatively. The results of the research has been done that the seller's responsibility to the buyer in the matter of the existence defect hidden in the trade laptop via internet, included the seller's responsibility and the manufacturer. Legal remedies can used by the buyer is to make a claim or demands of the warranty. Several sellers give the provisions about the warranty terms and conditions on each website, but there are also implied warranty at the seller's website. In the manufacturer’s warranty, the hidden defects was borne by the accordance with the warranty of their respective brands of laptops, because only problems related to damage as resulting from defective material or workmanship errors that can be borne within the period of warranty. The dispute resolution regarding the seller's responsibility use 2 ways: the first way that buyer return back the laptop to the seller with accompanied a description of the return of the laptop. The second way is buyer directly carry out the warranty claim in service center of the laptop brands.